Improvement of Songkok Production Process Through Defect Analysis Using Seven Tools and Failure Mode and Effect Analysis (FMEA) - Sofiyanurriyanti; Azwanda; Mahmud Basuki; Moh. Ainul Fais; Silvana Mohamad (Jurnal Inotera, 2026)
Product defects contribute to material waste, delays in delivery, and increased production costs. This study aims to identify the causes of product defects and reduce defect levels in songkok (traditional cap) production at CV PPI using the Seven Tools method and Failure Mode and Effect Analysis (FMEA). Data were collected in August 2025, revealing three main types of defects: untidy stitching (29.47%), inaccurate sizing (32.11%), and velvet surface defects (38.42%). Defect analysis was conducted using Seven Tools, while corrective actions were determined through FMEA by calculating the Risk Priority Number (RPN). The findings show that the highest RPN value was 210 for inaccurate sizing, followed by untidy stitching (RPN 168) and velvet surface defects (RPN 140). Improvement recommendations include stricter supervision during production, periodic evaluation of tools and materials, revision of inadequate Standard Operating Procedures (SOPs), and proper selection of velvet materials that meet quality standards to ensure product consistency and customer satisfaction.